Building pathways to peace : state-society relations and security sector reform - Ansorg, Nadine; Kurtenbach, Sabine (Cambridge : Cambridge University Press, 2023)
SSR is a key element of the transitions out of war, aiming at the establishment of accountable and legitimate institutions able to prevent and sanction the use of violence. While recognizing the need to include local actors, donor policies still focus mostly on the state as a provider of security. Second generation SSR has emphasized the need to include local communities and recognize the existence of non-state actors in the provision of security and justice. However, recognition is not enough. This Element promotes a radical re-think of SSR in the context of conflict and war. Guiding question for the considerations is how can security sector reform be set up and implemented to contribute to constructive and inclusive state-society relations, and build the path to long-lasting peace? This Element argues that a focus on functional equivalents, minorities, gender, and human rights is key for the design, implementation, and success of SSR.
Title from publisher's bibliographic system (viewed on 21 Nov 2023).
Keywords: Peace-building -- Social aspects